Exosomes as Next-Generation Carriers for Brain Drug Delivery: Engineering, Formulation, Characterization, and Neurotherapeutic Applications - D, Vani.; T, Ethiraj.; Ponnusamy, Sutha; R, Devi.; Philip, Aswathi Elisabeth (Pharmaceutical Nanotechnology, 2025)
<span class=
Keywords: Blood-brain barrier (BBB) penetration